2011
DOI: 10.1096/fasebj.25.1_supplement.lb196
|View full text |Cite
|
Sign up to set email alerts
|

The role of starch physicochemical properties in determining the Glycemic Index of potatoes

Abstract: Potatoes are a nutrient dense food, despite this, they are often thought of as unhealthy due to their purported high glycemic index (GI). Previously, we found a range of GI values for 8 different potato varieties when freshly cooked (range 52±4 to 81±9, p≤0.05) and that cooling cooked potatoes reduced GI by 20–50%. However, it is unclear if this effect can be seen in potatoes harvested in different years. Thus, the purpose of the present study was to examine the effect of variety and cooling on the GI of potat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…The GI values are known for only two genotypes in this study and are closely related to individual starch profiles. CV96044-3 was shown to have a consistent medium GI value (62 to 65 ± 6) compared to V1255-3, which ranged from medium to high GI (59 to 74 ± 6). , In this study, CV96044-3 was found to have low RDS levels, which is consistent with the lower GI values observed by Moreira and Wolever. , Low RDS levels are correlated with low to medium GI values . From a previous report, the GI value of Russet Burbank was 77± 9 .…”
Section: Results and Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The GI values are known for only two genotypes in this study and are closely related to individual starch profiles. CV96044-3 was shown to have a consistent medium GI value (62 to 65 ± 6) compared to V1255-3, which ranged from medium to high GI (59 to 74 ± 6). , In this study, CV96044-3 was found to have low RDS levels, which is consistent with the lower GI values observed by Moreira and Wolever. , Low RDS levels are correlated with low to medium GI values . From a previous report, the GI value of Russet Burbank was 77± 9 .…”
Section: Results and Discussionsupporting
confidence: 87%
“…CV96044-3 was shown to have a consistent medium GI value (62 to 65 ± 6) compared to V1255-3, which ranged from medium to high GI (59 to 74 ± 6). 47,48 In this study, CV96044-3 was found to have low RDS levels, which is consistent with the lower GI values observed by Moreira and Wolever. 47,48 Low RDS levels are correlated with low to medium GI values.…”
Section: Slowly Digestible Starch (Sds)supporting
confidence: 90%
See 3 more Smart Citations